Toward Semantic Event-Handling for Building Explainable Cyber-Physical Systems - Gernot Steindl; Tobias Schwarzinger; Katrin Schreiberhuber; Fajar J. Ekaputra (IEEE Open Journal of the Industrial Electronics Society)
In the context of cyber-physical systems (CPS), understanding system behaviors is crucial for ensuring reliability, efficiency, and trust. However, due to the increasing complexity of the modern CPS, gaining such understanding is becoming more challenging. In this article we provide a foundation for explaining system behavior through detected system events. To this end, the article proposes a technology-agnostic, semantic event-handling module to address the challenge of enhancing explainability within CPS. This module is designed to be part of the common architecture for Explainable CPS and, therefore, can be integrated seamlessly into existing CPS frameworks by providing different interfaces to access detected events. Two case studies in the smart building and smart grid domain are carried out to demonstrate the feasibility and efficacy of the approach, utilizing an open-source software stack for the prototypical implementation. A qualitative evaluation of the proposed approach, based on the ISO/IEC 25010:2023, was used to analyze the software design. Our evaluation result shows that the semantic event-handling module is appropriate as a generic approach to handling events within a CPS. The module becomes a foundation for incorporating explainability into the system, which is needed as a foundation to ensure human trust and enable informed decision-making.